Serum and urine TNF-like weak inducer of apoptosis, monocyte chemoattractant protein-1 and neutrophil gelatinase-associated lipocalin as biomarkers of disease activity in patients with systemic lupus erythematosus. (April 2020) - Mirioglu, S; Cinar, S; Yazici, H; Ozluk, Y; Kilicaslan, I; Gul, A; Ocal, L; Inanc, M; Artim-Esen, B
Objectives: TNF-like weak inducer of apoptosis (TWEAK), monocyte chemoattractant protein-1 (MCP-1) and neutrophil gelatinase-associated lipocalin (NGAL) are proinflammatory cytokines/chemokines that are considered as potential biomarkers reflecting disease activity in systemic lupus erythematosus (SLE). In this study, we aimed to investigate the association of serum (s) and urine (u) levels of TWEAK, MCP-1 and NGAL with disease activity in both renal and extra-renal SLE. Methods: Thirty active patients with SLE (15 renal and 15 extra-renal) were recruited. Thirty-one inactive patients with SLE (16 renal and 15 extra-renal), 14 patients with ANCA-associated vasculitis (AAV) all of whom had active renal involvement and 20 healthy volunteers were selected as control groups. Serum and urine levels of TWEAK, MCP-1 and NGAL were tested using ELISA. Results: Serum and urine levels of TWEAK and NGAL were significantly higher in the active SLE group compared to the inactive SLE group (sTWEAK p  = 0.005; uTWEAK p  = 0.026; sNGAL p  < 0.001; uNGAL p  = 0.002), whilst no significant differences regarding serum and urine MCP-1 levels were observed ( p  = 0.189 and p  = 0.106, respectively). uTWEAK ( p  = 0.237), sMCP-1 ( p  = 0.141), uMCP-1 ( p  = 0.206), sNGAL ( p  = 0.419) and uNGAL ( p  = 0.443) levels did not differ between patients with active renal and extra-renal SLE. Serum TWEAK was higher in patients with active renal SLE ( p  = 0.006). There were no differences between active renal SLE and active renal AAV. Levels of all biomarkers were correlated with the SLE Disease Activity Index. Conclusion: sTWEAK, uTWEAK, sNGAL and uNGAL are biomarkers showing disease activity in SLE. However, our results implicate that these biomarkers may not be specific for SLE, and can be elevated in patients with active renal involvement of AAV.